Journalistic Coverage Patterns: Generic Frames and Level Frames at the 2016 Peruvian Presidential Elections - Macassi Lavander, Sandro (2019)
This text reviews the literature on frame analysis, paying attention to the relationship between frames and politics in electoral processes. The studies on level frames and on generic frames are discussed. The types of frames are analyzed: level frames and generic frames. The use of both frames is compared in the Peruvian elections of 2014 and 2016, emphasizing the presidential elections of 2016. Likewise, it is analyzed if the use of these frames show differences between the types of media. The study was based on the analysis of 5112 electoral news from 20 programs and radio, press and television news spaces. The findings show that there is a pattern of coverage of the use of frames that persists from one election to another. But, there are differences in the use of frames from the first phase to the second round of the electoral campaign.Like the studies on coverage in other countries, in the Peruvian case the use of “conflict frames” is common, However, it differs from the international pattern because in the Peruvian case there is a more frequent use of the “frame of morality”. This is a particular feature of Peruvian newspaper coverage. Therefore, the coverage of the Peruvian media follows globalized production patterns together with schemes typical of the national journalistic culture, generating a hybridation of news production patterns.